PENGARUH LEMBAR KEGIATAN SISWA BERORIENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN FISIKA TERHADAP PENCAPAIAN KOMPETENSI SISWA - Muhammad Bohori; Amali Putra; Pakhrur Razi (Universitas Negeri Padang, 2015)
Material of education must be prepared by teacher to do activities of education that students as center of it. The porpuse of the resacrch is to know how influence material of education like work sheet that have oriented to do scientific approach on physics study to attainment student’s competences. This research was an experimental research randomized control group only design. The population of this research were all of the students of SMAN 15 Padang in the first semester of academic year 2014/2015. Research data include the attainment of students from three aspects : attitude, knowledge, and skill. Aspects of the assessment instrument in the form of sheet attitude observation, self assessment sheet, and peer assessment sheet. Assessment instrument aspects of knowledge in the form of multiple choice test and aspects of skills in the rubric scoring sheet. Based on research that has been done, the result of research thet the average value of aspects attitude in the experimental class was 90,02 higher than control class was 87,73. The average value of the aspects knowledge in the experimental class was 77,12 higher control class was 87,73. The Average value aspects of skill in the experimental class was 82,34 higher than control class was 76,7. The research results were analyzed using t test at the 0,05 significance level. The result of study showed that there are significance difference between the students attainment of experimental class with the control class. This difference is due to the influence of the use of student activity sheet oriented scientific approach